Advancing Precision Medicine: Recent Innovations in Gene Editing Technologies - Abhijith Koodamvetty; Saravanabhavan Thangavel (Advanced Science)
Abstract The advent of gene editing has significantly advanced the field of medicine, opening new frontiers in the treatment of genetic disorders, cancer, and infectious diseases. Gene editing technology remains a dynamic and promising area of research and development. Recent advancements in protein and RNA engineering within this field have addressed critical issues such as imprecise edits, poor editing efficiency, and off‐target effects. Advancements in delivery methods have allowed the achievement of therapeutic or even selection‐free gene editing efficiency with reduced toxicity in primary cells, thereby enhancing the safety and efficacy of gene manipulation. This progress paves the way for transformative changes in molecular biology, medicine, and other fields. This review provides a comprehensive overview of the advancements in gene editing techniques, focusing on prime editor proteins and their engineered variants. It also explores alternative systems that expand the toolkit for precise genomic modifications and highlights the potential of these innovations in treating hematological disorders, while also discussing the limitations and challenges that remain.